Impact of the COVID-19 pandemic on intracranial aneurysm treatment and associated Outcomes: A nationwide US-based study - Abdul Karim Ghaith; Victor Gabriel El-Hajj; Jorge Rios-Zermeno; Elena Greco; David A. Miller; Erik H. Middlebrooks; William D. Freeman; Adrian Elmi-Terander; Sukhwinder S. Sandhu; Rabih G. Tawk (Interdisciplinary Neurosurgery, 2024)
Objective: Limited data on the treatment and outcomes of patients with intracranial aneurysms (ICAs) in the (coronavirus disease 2019) COVID-19 era is available. Our objective was hence to investigate the impact of the pandemic on the overall complication rate and postprocedural ischemic strokes specifically, in patients treated for ICAs. Methods: The National Inpatient sample database was used. The main outcomes were the occurrence of postprocedural ischemic strokes, as well as death, non-routine discharge, total charges (US dollars), and length of stay (days). Propensity score matching was applied to compare the pre- and COVID-19 periods. Trends were assessed using piecewise joinpoint regression with the Mann-Kendall test. Results: A total of 57,715 patients were included in the study. The mean age was 65 years, with most of the patients (69.9 %) being females. After matching, no differences in length of stay (p = 0.266), non-home discharge (p = 0.475), and in-hospital mortality rates (p = 0.305) between the two periods were found. However, the overall complication rate was significantly higher during the pandemic (31.1 % vs. 28.3 %; p < 0.001). Patients hospitalized after treatment of ICAs during the COVID-19 pandemic had significantly higher odds of ischemic strokes (OR 1.13; 95 % CI 1.05 to 1.22; p = 0.03), even when adjusting for other factors. Conclusions: There is no denying that the COVID-19 pandemic has significantly impacted the healthcare system in several aspects. One aspect highlighted in this study, patient outcomes, was especially notable among patients’ receiving treatment for ICAs. Our results suggest a correlation between the COVID-19 pandemic and postprocedural complications, of which ischemic strokes were the most notable.